Pengajaran Rasul Paulus Tentang Memilih Pasangan Hidup Berdasarkan 2 Korintus 6:11-18 - Yohanis Banamtuan; Paulus Sentot Purwoko; Sri Wahyuni (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2022)
In general, researchers who discuss the Apostle Paul's teaching about spouses only base it on one verse, namely 2 Corinthians 6:14 and ignore the text of the title in this verse. The verses before and after, namely 2 Corinthians 6:11-18 have not been studied, that's why researchers are interested in discussing them. Even though this verse is very fundamental for young Christians to know, not all Christian youths read or hear this topic preached intensely in church or in various other Christian services. Likewise, Christian parents don't all read this verse or hear it preached, so parents don't teach their children the principles and standards of God's word for their children in finding a life partner. As a result, it often happens that there are believers who leave their faith in the Lord Jesus because of mistakes in choosing a life partner. The purpose of this research is to find the basic principles of the Apostle Paul's teaching about choosing a life partner based on 2 Corinthians 6:11-18, so that both Christian youths and Christian parents can make this teaching of the Apostle Paul the basic principle and standard. in choosing a life partner according to God's Word. The method used in this research is qualitative with a literature study approach. The results of research on the teachings of the Apostle Paul about life partners based on 2 Corinthians 6:11-18 are life partners that God wants are balanced, namely having faith and maintaining holiness until the holy wedding day.